THE IMPORTANCE OF ENTREPRENEURS IN ROAD CONSTRUCTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is devoted to a scientific analysis of the role of entrepreneurs in the field of road construction and their contribution to economic and social development. In recent years, the modernization of road and transport infrastructure in Uzbekistan, the development of international transport corridors through large investment projects has become one of the priority areas of state policy. The active participation of the nonstate sector in these processes, in particular the contribution of entrepreneurs to road construction, is of great importance. The modernization of construction technologies by entrepreneurs, the involvement of modern mechanisms and innovative technical means, and the adaptation of quality standards to international requirements allow for the integrated development of road networks.